Comparative ungulate dynamics: the devil is in the detail. - Clutton-Brock, T; Coulson, T (2002)
Attempts to relate species differences in population dynamics to variation in life histories rely on the assumption that the causes of contrasts in demography are sufficiently simple to be derived from first principles. Here, we investigate the causes of contrasts in dynamics between two ungulate populations on Hebridean islands (red deer and Soay sheep) and show that differences in stability, as well as in the effects of variation in density and climate, are related to differences in timing of reproduction relative to seasonal variation in resource abundance. In both populations, attempts to predict changes in population size sufficiently accurately for the results to be useful for management purposes require a knowledge of the responses of different age and sex categories to changes in density and climate, as well as of population structure.